Pengaruh GCG Dan Likuiditas Terhadap Kinerja Keuangan Perusahaan Dengan CSR Sebagai Pemoderasi Pada Sub Sektor FOOD and BEVERAGE Yang Terdaftar di BEI Periode 2021-2023 - Noviandini, Aurelia; Endah Fajar Hidayah, Nur (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
The purpose of this study is to analyze the influence of Good Corporate Governance and liquidity on financial performance, with Corporate Social Responsibility as a moderating factor, in companies within the Food and Beverage Sub-sector. This study used Food and Beverage Sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period as its subject. The research method used was quantitative, using SPSS for data analysis. The data source used in this study was secondary data. The population in this study was 78 Food and Beverage Sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The sample used a purposive sampling technique, resulting in 26 companies. The data collection technique used in this study was Document Study. Data analysis techniques used descriptive analysis, multiple linear regression, t-test, f-test, coefficient of determination test, and Moderating Regression Analysis (MRA). The results of this study indicate that the Board of Directors has no significant effect on Financial Performance. The Independent Board of Commissioners has a significant positive effect on Financial Performance. Liquidity has a significant positive effect on Financial Performance. Corporate Social Responsibility is unable to moderate the Board of Directors' influence on Financial Performance. Corporate Social Responsibility is unable to moderate the Independent Board of Commissioners' influence on Financial Performance. Corporate Social Responsibility is unable to moderate Liquidity on Financial Performance.